Performance lifestyle provision in a multi-disciplinary team: A qualitative investigation of current practice and future progression - Killoughery, I.; Yiannaki, C.; Rhodes, D. (International Journal of Sports Science & Coaching, 2025)
Performance Lifestyle (PL) services have the potential to make a novel contribution to athlete development, yet has limited research, notably examining the experiences of PL practitioners. This study explored PL practitioner perspectives to highlight current barriers and limitations in service delivery, whilst highlighting good practice. Six semi-structured interviews were conducted. Each participant supported athletes competing at professional, international, or Olympic levels. All participants were employed to deliver PL services with an average of 10.83 (±6.71) years` experience. Reflexive thematic analysis was chosen to analyse the data with three main themes constructed. `Creating an informed environment` illustrates environments that lack understanding regarding the nature, scope and value of PL services. `Optimising the role of PL practitioners` seeks to identify best practice and explore common issues faced by practitioners. `Improving practitioner and coach education` indicates a need for enhanced competencies and contemporary training for future practitioners and coaches. Findings provide unique insights into the experiences of practitioners and suggest that PL delivery, and its impact, is limited by several factors. This study discusses the contemporary implications of these issues and applied recommendations for future PL provision within high-performance sport environments.